International study of the place of death of people with cancer: a population-level comparison of 14 countries across 4 continents using death certificate data - Cohen, J; Pivodic, L; Miccinesi, G; Onwuteaka-Philipsen, B D; Naylor, W A; Wilson, D M; Loucka, M; Csikos, A; Pardon, K; Van den Block, L; Ruiz-Ramos, M; Cardenas-Turanzas, M; et al. (British journal of cancer, 2015)
BACKGROUND: Where people die can influence a number of indicators of the quality of dying. We aimed to describe the place of death of people with cancer and its associations with clinical, socio-demographic and healthcare supply characteristics in 14 countries. METHODS: Cross-sectional study using death certificate data for all deaths from cancer (ICD-10 codes C00-C97) in 2008 in Belgium, Canada, Czech Republic, England, France, Hungary, Italy, Mexico, the Netherlands, New Zealand, South Korea, Spain (2010), USA (2007) and Wales (N=1,355,910). Multivariable logistic regression analyses evaluated factors associated with home death within countries and differences across countries. RESULTS: Between 12% (South Korea) and 57% (Mexico) of cancer deaths occurred at home; between 26% (Netherlands, New Zealand) and 87% (South Korea) occurred in hospital. The large between-country differences in home or hospital deaths were partly explained by differences in availability of hospital- and long-term care beds and general practitioners. Haematologic rather than solid cancer (odds ratios (ORs) 1.29-3.17) and being married rather than divorced (ORs 1.17-2.54) were most consistently associated with home death across countries. CONCLUSIONS: A large country variation in the place of death can partly be explained by countries' healthcare resources. Country-specific choices regarding the organisation of end-of-life cancer care likely explain an additional part. These findings indicate the further challenge to evaluate how different specific policies can influence place of death patterns.
Keywords: novorozenec; Infant, Newborn; Infant; Humans; kojenec; lidé středního věku; Palliative Care; dítě; Child; Female; Aged; mladý dospělý; dospělí; úmrtní listy; péče o umírající; senioři; lidé; Death Certificates; dlouhodobá péče; předškolní dítě; Adult; ženské pohlaví; Hospitals; Male; Middle Aged; Adolescent; Neoplasms; nemocnice; paliativní péče; Aged, 80 and over; Terminal Care; nádory; Cause of Death; Cross-Sectional Studies; Young Adult; senioři nad 80 let; příčina smrti; mužské pohlaví; Child, Preschool; Long-Term Care; průřezové studie; mladiství